Lawe Wĕnang Singid: Benang Merah Kontinuitas Penanganan Pagĕblug dalam Perspektif Kesusastraan Jawa - Taruna Dharma Jati; Muhammad Ibnu Prarista; Zalsabila Purnama; Zakariya Pamuji Aminullah (Perpustakaan Nasional RI, 2022)
The collective memory, which was scripted in Javanese literature, indicates that pagĕblug happened in the past. However, the public does not know its information since the primary resource is indecipherable, followed by the rapid growth of science and technology. Whereas in Javanese literature, there is knowledge about tracing and handling a pagĕblug. Therefore, This study has three main objectives: (a) Examine the handling of pagĕblug in Java based on primary sources taken from Javanese textual and non-textual archives; (b) Reveal the common thread of continuity in handling pagĕblug cosmologically and physically; (c)Propose a draft of strategy for dealing with pagĕblug in the present.The research conducted in descriptive-qualitative-interpretative, utilizing philological and oral approaches. The data was compiled using blended methods consisting of literature study, source observation, manuscript reading, and interview with experts. The results indicate that Javanese literature contains knowledge of cosmological and physical handling of pagĕblug. Cosmologically, the common thread of continuity in handling pagĕblug in Javanese literature is derived from a concept of respecting human relationships with others, nature, and God. Likewise, physically, it is advised to have a clean and healthy living, even encouragement to self- quarantine for the infected people. The common thread for the continuity of pagĕblug handling potentially can be implemented by the government in formulating disease regulations amid the current Covid-19 pandemic.